Self-employment and earning inequality - Falter, Jean-Marc (Journal of Income Distribution®, 2007)
The present study attempts to explain the difference in observed earning inequalitybetween self-employment and wage-employment in Switzerland in 1992, 1995and 2000. We use several measures of inequality in order both to determine the factorsaffecting income dispersion in the two groups and to identify the variables thatdrive the earning inequality differential. Thus, we make use of discrete decompositiontechniques and of a regression-based method. The latter allows us to introducea selection term in our decompositions which is of crucial importance in the case ofself-employment. Our results indicate that education- and age-related variables, likework experience and tenure, are the most important factors explaining the inequalitylevel in both groups. The importance of these factors seems, however, to be larger inthe wage-employment sector. The reason may lie in the process of selection into selfemploymentrather than in the differences in the returns to characteristics between thetwo sectors.